Research on Service Learning in Spanish scientific production: a systematic review - Redondo-Corcobado, Paloma; Fuentes, Juan Luis (Revista Complutense de Educación, 2020)
Growing interest in service-learning methodology can be noticed nowadays on different educative actualities, both from theoretical and research levels as from implementation done in diverse levels and contexts. This article shows a systematic review of scientific production about service-learning in Spanish scientific journals contained in 2017 on Journal Citation Reports and Scimago Journal & Country Rank and those journals that were awarded with the quality seal on the evaluation calls carried out by Spanish Foundation for Science and Technology (FECYT). That systematic review consists of an analysis on each one of the publications that compose it, of descriptive extrinsic variables to the scientific process, methodological variables, variables referred to the participants and variables referred to the methodology service-learning projects. Results show basically an increase of service-learning publications on the last four years, almost all of them developed over the academic field, mainly on Child Education degree and Primary Education degree, the predominance of theoretical and qualitative studies over quantitative ones and a greater focus on learning variables over service related ones. This way, analysis reveals an objective picture of the situation of educational research on service-learning and the identification of emerging challenges in this field of knowledge and educational practices, which could be crucial to get a permanent and solid scientific status.
Keywords: service-learning; systematic review; civic education; socio-communitarian development